MANAGEMENT OF COMPETENCE DEVELOPMENT OF THE HIGHER-EDUCATION TEACHING PERSONNEL - Barkalov, Sergey; Kalinina, Natalia; Nasonova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The urgency of the work is determined by the need to develop new approaches to the assessment process and to increase the level of competence of the teaching staff of the institution, which is the most important factor of its competitiveness. The object of the study is the management system of the teaching staff of the higher education institution. The subject of the study are the models and methods of managing the level of competence of the faculty.Research objective is to increase the level of competence of the higher-education teaching personnel.The methods of system analysis, mathematical programming, graph theory are used in the paper.